PEMBERDAYAAN KADER DAN EDUKASI KEPADA REMAJA PUTRI DALAM UPAYA PENCEGAHAN STUNTING DI DESA BOROKANDA WILAYAH KERJA PUSKESMAS KOTA RATU - rifatunnisa; Cahyani, Sisilia L.; Sekunda, Maria S.; Dhoke, Maria F. L. (Kelimutu Nursing Journal, 2023)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1,000 days of life (HPK). It is important to reduce stunting as early as possible to avoid long-term detrimental impacts such as stunting children's growth and development. The aim of this community service is to empower cadres in providing education to young women about preventing stunting in Borokanda Village, Ratu City Health Center Working Area, which includes increasing posyandu cadres' knowledge about Stunting, taking into account reproductive health, parenting patterns, eating patterns, clean and healthy living behavior during the first 1000 days of life. Increasing knowledge of young women about stunting by paying attention to reproductive health, parenting, eating patterns, clean and healthy living behavior during the first 1000 days of life, which is educated by posyandu cadres who have received training on how to provide counseling to young women. This community service activity was carried out through several methods, including: lectures/counseling, booklets, training and mentoring for posyandu cadres in educating young women and the results obtained were an increase in the knowledge of young women with good post test results of 93%.